2008
DOI: 10.1002/msc.142
|View full text |Cite
|
Sign up to set email alerts
|

The FOOTSTEP self‐management foot care programme: Are rheumatoid arthritis patients physically able to participate?

Abstract: Just over half the patients in this present cohort may be physically able to undertake some aspects of self-managed foot care, including nail clipping and filing, callus filing and daily hygiene and inspection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…Our results also highlight that social support and physical ability may influence this need, as this subgroup were more likely to be living alone and to have osteoarthritis in the knees or back. Physical barriers to self-management of foot problems have previously been reported by Campbell et al [29], who found that 63% of older people who had been discharged from podiatry services were unable to care for their own feet due to an inability to bend, hand weakness and poor eyesight, and by Semple et al [30], who found that nearly half of a sample of 30 people with rheumatoid arthritis (mean age 61 years) were unable to self-manage foot problems due to impaired grip strength and difficulty reaching. These findings suggest that although self-management of foot problems has been shown to be effective in older people [31], there are specific subgroups of older people that require professional assistance from foot health specialists.…”
Section: Discussionmentioning
confidence: 93%
“…Our results also highlight that social support and physical ability may influence this need, as this subgroup were more likely to be living alone and to have osteoarthritis in the knees or back. Physical barriers to self-management of foot problems have previously been reported by Campbell et al [29], who found that 63% of older people who had been discharged from podiatry services were unable to care for their own feet due to an inability to bend, hand weakness and poor eyesight, and by Semple et al [30], who found that nearly half of a sample of 30 people with rheumatoid arthritis (mean age 61 years) were unable to self-manage foot problems due to impaired grip strength and difficulty reaching. These findings suggest that although self-management of foot problems has been shown to be effective in older people [31], there are specific subgroups of older people that require professional assistance from foot health specialists.…”
Section: Discussionmentioning
confidence: 93%
“…The potential value of group education was thought to be in providing a supportive environment for general foot health information and self-management education, if planned and facilitated appropriately. The implementation of group foot health self-management programmes for people with RA may be an effective method of delivery, providing members can perform self care tasks, such as basic nail cutting [44]. …”
Section: Discussionmentioning
confidence: 99%
“…In patients with RA and foot problems, approximately half are unable to manage their own feet due to problems with reach and grip strength (Semple et al 2008). Podiatrists can assist patients and their family or carers to help them maintain good standards of personal foot hygiene.…”
Section: Basic Foot Hygiene Self-management and Advicementioning
confidence: 99%